2013
DOI: 10.2478/johh-2013-0011
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influences water sorptivity of soil aggregates

Abstract: Abstract:The aim of this study was to determine the potential development of water sorptivity of soil aggregates by heating. Soil aggregates were sampled from arable layer of 5 Polish soils: Haplic Luvisol 1 from Czesławice, Haplic Luvisol 2 from Wierzchucinek, Haplic Cambisol from Felin, Gleyic Mollic Cambisol from Chylice, and Haplic Phaeozem from Grabiec. Three aggregates of each soil type with minimum diameter between 4 and 10 mm were heated in the oven for at least 3 hours at temperatures 20, 100, 200, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In recent years, noteworthy progresses have been carried out in understanding factors affecting SWR. Water repellency is conditioned by soil properties such as organic matter content and quality (Leelamanie and Karube, ; Atanassova and Doerr, ), texture (Roberts and Carbon, ; Giovannini and Lucchesi, ; Mataix‐Solera et al ., ), aggregates (Zavala et al ., ; Jordán et al ., ; Mataix‐Solera et al ., ), acidity and mineralogy of the clay fraction (Dlapa et al ., ; Mataix‐Solera et al ., ; Zavala et al ., ; Mirbabaei et al ., ), microbial activity (Savage et al ., ; Jex et al ., ), water content Poulenard et al ., ; Regalado and Ritter, ; Lichner et al ., ; De Jonge et al ., ) and seasonal variations (De Jonge et al ., ; Doerr and Thomas, ; Leelamanie and Karube, ; Zavala et al ., ; Czachor and Lichner, ).…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, noteworthy progresses have been carried out in understanding factors affecting SWR. Water repellency is conditioned by soil properties such as organic matter content and quality (Leelamanie and Karube, ; Atanassova and Doerr, ), texture (Roberts and Carbon, ; Giovannini and Lucchesi, ; Mataix‐Solera et al ., ), aggregates (Zavala et al ., ; Jordán et al ., ; Mataix‐Solera et al ., ), acidity and mineralogy of the clay fraction (Dlapa et al ., ; Mataix‐Solera et al ., ; Zavala et al ., ; Mirbabaei et al ., ), microbial activity (Savage et al ., ; Jex et al ., ), water content Poulenard et al ., ; Regalado and Ritter, ; Lichner et al ., ; De Jonge et al ., ) and seasonal variations (De Jonge et al ., ; Doerr and Thomas, ; Leelamanie and Karube, ; Zavala et al ., ; Czachor and Lichner, ).…”
Section: Introductionmentioning
confidence: 98%
“…A number of studies have shown that biochar is a promising soil amendment material which has the potential to mitigate climate change through increasing soil organic carbon (SOC) content and by improving soil quality, thus contributing to higher yield from smaller area (Laird et al 2010;Zhang et al 2012). Application of organic materials such as biochar is reported to improve soil chemical (Liang et al 2006), physical (Atkinson et al 2010;Czachor & Lichner 2013) and biological properties (Lehmann et al 2011), biochar has also been shown to increase crop yields, reduce GHGs and increase soil carbon sequestration (Lehmann et al 2006). Biochar added to arable soils exerts some control over N dynamics (Clough et al 2013) and has the potential to reduce N2O emissions from soils (Hüppi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Soil 3 organic carbon (SOC) content is one of the qualitative parameters of the soil humus regime (Howard & Howard 1990). Soil structure is one of the soil's most important physical properties, critically important for many soil environmental processes (Czachor & Lichner 2013;Garbout et al 2013;Kodešová et al 2015;Leelamanie & Mapa 2015). Soil structure is the key factor regulating soil function, its ability to support plant and animal life, and moderate environmental quality (Bronick & Lal 2005).…”
Section: Introductionmentioning
confidence: 99%